Ensaios sobre os efeitos da internacionalização na estrutura de capital e estrutura de propriedade de multinacionais latino-americanas - Pereira, Vinícius Silva (2013)
This thesis examines three gaps that have not been discussed in the literature. The gaps relate to the effects of internationalization on capital structure and ownership structure of multinational companies. Therefore, three essays about the effects of internationalization were prepared. The first essay examined the effects of entry modes on debt, the second the effects of internationalization in the forms of indebtedness and the third the effects of internationalization on the ownership structure. Data form domestic and multinational publicly traded companies in Latin America from 2007 to 2011 were assembled into panel data with test and control variables for each essay. The results of the first essay indicate that the entry modes are relevant to determine the debt level of multinational and complement the studies based on upstream-downstream hypothesis. It also showed that companies with equity entry modes tend to be more indebted in the total and long term than companies with non-equity entry modes, reinforcing explanations given by the static trade-off theory, and less indebted in the short term, urging agency and pecking order theories. The results of the second essay show that the degree of internationalization: (i) increases the debt level of almost all debts provided by financial agents (banks), as hypothesized upstream-downstream and reduce the debt provided by non-financial (trade-credit), as suggested by the theory of financial constraint, (ii) has no effect on debt maturity (iii) different than expected, does not increase debt via national development bank (encouraged loans), (iv) was relevant to change the composition of indebtedness of multinationals compared to domestic firms and (v) the entry modes on internationalization does not affect the composition of debt. In the third essay, the main finding result was that the most internationalized companies and equity entry mode have lower levels of ownership concentration. Another important result of the third essay was that there is an unexplored simultaneity in determining the level of internationalization and concentration of ownership. Both the results of the third essay are supported by the Resource Based View countering the traditional view of agency theory.